Adsorptive removal of lead ion from water using banana stem scutcher generated in fiber extraction process - Santosh Kokate; Karuppasamy Parasuraman; Halan Prakash (Results in Engineering, 2022)
Lignocellulosic biomass-based adsorbents for removal of heavy metal ions from water have been reported. Importantly, a solid biomass waste known as Banana Stem Scutcher (BSS) is generated in banana stem fiber (BSF) extraction from lignocellulosic rich banana stem (BS). Here, for the first time, we report BSS characterization, and its ability for adsorption of lead (Pb(II)) ion from water. The maximum adsorption capacity for Pb(II) ion removal by BSS was determined to be 179.9 mg g−1. BSS was recycled five times without any significant loss in adsorption performance. Pb(II) ion adsorption onto BSS is exothermic (ΔH = −70.55 kJ mol−1), and spontaneous (ΔG = −3.52 kJ mol−1 at 303 K) with energy of activation as, 95.95 kJ mol−1. Further, interaction between Pb(II) ion and functional groups of BSS was confirmed by XPS and FTIR results. The relative cellulose content in BSS (74.25%) was higher than the BS (57.85%), as well as BSF (60.36%). The higher accessible cellulosic content in BSS was proposed for the enhanced Pb(II) ion adsorption by BSS, compared to BS and BSF. The study highlights a low cost and chemical free, mechanical based treatment of biomass useful to produce effective biomass-based adsorbents for removal of metal ions.